2016
DOI: 10.1016/j.bcmd.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with ipriflavone decreases hepatic iron stores in wild type mice

Abstract: Hepcidin, a peptide produced in the liver, decreases intestinal iron absorption and macrophage iron release by causing degradation of the iron exporter, ferroportin. Because its levels are inappropriately low in patients with iron overload syndromes, hepcidin is a potential drug target. We previously conducted a chemical screen that revealed ipriflavone, an orally available small molecule, as a potent inducer of hepcidin expression. To evaluate ipriflavone's effect on iron homeostasis, we placed groups of 5-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…These genes were validated by RNAi and small-molecule testing was applied to identify the corresponding drugs as hepcidin modulators. This approach complements and extends previously reported drug screens in search for hepcidin regulators, 39 , 40 in that it starts with a ‘pre-selected’ set of drugs based on a comprehensive RNAi approach, applies time-and dose-response experiments, and involves validations in primary cells and mice. With this approach we identified four compounds that modulate hepcidin mRNA levels in primary hepatocyte models ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 81%
“…These genes were validated by RNAi and small-molecule testing was applied to identify the corresponding drugs as hepcidin modulators. This approach complements and extends previously reported drug screens in search for hepcidin regulators, 39 , 40 in that it starts with a ‘pre-selected’ set of drugs based on a comprehensive RNAi approach, applies time-and dose-response experiments, and involves validations in primary cells and mice. With this approach we identified four compounds that modulate hepcidin mRNA levels in primary hepatocyte models ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 81%
“…The treated mice displayed a significant reduction in liver iron content of approximately 40% compared to control untreated mice. Ipriflavone also resulted in an approximate two-fold increase in hepcidin mRNA levels [151]. The hepcidin inducing effect of vorinstat was further confirmed in another study using HUH7 and primary hepatocytes from both human and mice origin [100].…”
Section: Small Molecule Hepcidin Agonistsmentioning
confidence: 76%
“…Of note, ipriflavone and vorinostat were found to elicit an effect on hepcidin expression at concentrations 10-fold lower than those required for genistein [127]. Due to the higher potency of ipriflavone, C57BL/6 male mice were treated with increasing concentrations of ipriflavone for 50 days to determine changes in iron content, hepcidin and ferroportin expression levels [151]. The treated mice displayed a significant reduction in liver iron content of approximately 40% compared to control untreated mice.…”
Section: Small Molecule Hepcidin Agonistsmentioning
confidence: 99%
“…The differences in effect of these two similar polyphenols on iron absorption indicate the complexity of responses to polyphenols. Furthermore, Zhen et al [ 17 ] and Patchen et al [ 40 ] showed that genistein, a main polyphenol from soya, and ipriflavone, synthetic analog derived from abundant dietary polyphenol daidzein, respectively, both strongly promote hepcidin expression in vivo. Recent studies by Grillo et al [ 41 ] and Zhang et al [ 42 ] indicate that natural products could have a major role in iron metabolism and may have potential in therapy of iron metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%